ANALISIS PENERAPAN AKUNTANSI KOPERASI BERDASARKAN SAK ETAP : (Studi Kasus Koperasi Trilogi Mandiri Sejahtera) - Hakiki Rahmi; Lely Dahlia (FEB-UP Press, 2022)
ABSTRACT This study aims to analyze the presentation and preparation of the financial statements of the Mandiri Sejahtera Trilogy Cooperative in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This study uses a qualitative method with a descriptive analysis approach, primary data collection techniques through observation, interviews, and documentation, and secondary data techniques through structural information sources, history, and financial reports of the Mandiri Sejahtera Trilogy Cooperative. The results of this study indicate that the Mandiri Sejahtera Trilogy Cooperative has two business units, namely a savings and loan business and a shop business unit. In the financial statements of the savings and loan units and store business units, the presentation of financial statements in 2019 and 2020 is almost in accordance with SAK ETAP. However, there are several components of the financial statements in which the two business units of the Mandiri Sejahtera Trilogy Cooperative do not carry out the transaction.